UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PICTURE AND PICTURE UNTUK SISWA KELAS III PADA SDN BINTURU KECAMATAN KELUA KABUPATEN TABALONG - Ristiawati Ristiawati (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2012)
A study concerning the application of the picture and picture on the earth's surface appearance of learning materials. The application of the model picture and picture are expected to impact positively on students' interest and motivation in learning, so as to increase student learning outcomes in the material. This study aims to (1) increase the activity of students (2) improve science learning outcomes. The study used a classroom action research with 2 cycles. Each cycle consists of stages of planning, action, observation, and reflection. Subjects were third grade students of SDN Binturu totaling 26 students. The research instrument in the form of test instruments test objective type questions and non-test instruments such as observation and interviews. The research concludes (1) student activities has increased from 58.04% in Cycle 1 to 87.5% in Cycle 2 (2) student learning outcomes increased from 53.85 to 80.77 at cycle 1 to cycle 2.Keywords: picture and picture, the appearance of the surface of the earth, learning outcomes